Brucella neotomae infection in humans, Costa Rica - BARQUERO-CALVO, ELIAS (2017)
Several species of Brucella are known to be zoonotic, but B. neotomae infection has been thought to be limited to wood rats. In 2008 and 2011, however, B. neotomae was isolated from cerebrospinal fluid of 2 men with neurobrucellosis. The nonzoonotic status of B. neotomae should be reassessed.